Evaluation and Redesign of Telkom University’s Open Library Website Interface Using the Goal Directed Design (GDD) Method - Zian Alfaen; Indra Lukmana Sardi; Monterico Adrian (Forum Kerjasama Pendidikan Tinggi, 2022)
As a university with World Class University quality, Telkom University provides information services with a website as the main source of libraries for its students. The website is called Open Library which provides information on all library collections owned by Telkom University which are open and can be loaned. One of the missions of this website is